If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6)(h) + 2(h)(17) + 2(6)(17) = h Multiply 2 * 6 12h + 2(h)(17) + 2(6)(17) = h Reorder the terms for easier multiplication: 12h + 2 * 17h + 2(6)(17) = h Multiply 2 * 17 12h + 34h + 2(6)(17) = h Multiply 2 * 6 12h + 34h + 12 * 17 = h Multiply 12 * 17 12h + 34h + 204 = h Reorder the terms: 204 + 12h + 34h = h Combine like terms: 12h + 34h = 46h 204 + 46h = h Solving 204 + 46h = h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 204 + 46h + -1h = h + -1h Combine like terms: 46h + -1h = 45h 204 + 45h = h + -1h Combine like terms: h + -1h = 0 204 + 45h = 0 Add '-204' to each side of the equation. 204 + -204 + 45h = 0 + -204 Combine like terms: 204 + -204 = 0 0 + 45h = 0 + -204 45h = 0 + -204 Combine like terms: 0 + -204 = -204 45h = -204 Divide each side by '45'. h = -4.533333333 Simplifying h = -4.533333333
| 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= | | 0.29=logx | | x=log(3)(48) | | 3/4t-6=1/3t-1 | | 3/2t-6=1/3t-1 | | nx+b=6(x-n)forx | | nx+b=6(x-n) | | 3x(x+4)=3(x-1) | | 70-1.5(4)= | | 6y-15=3y+6 | | 144s^2-225c^2=0 | | s^2-2s+16=0 |